2017
DOI: 10.1007/s00418-017-1604-2
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulating in vivo-like plasticity of glioma cell invasion along blood vessels and in astrocyte-rich stroma

Abstract: Diffuse invasion of glioma cells into the brain parenchyma leads to nonresectable brain tumors and poor prognosis of glioma disease. In vivo, glioma cells can adopt a range of invasion strategies and routes, by moving as single cells, collective strands and multicellular networks along perivascular, perineuronal and interstitial guidance cues. Current in vitro assays to probe glioma cell invasion, however, are limited in recapitulating the modes and adaptability of glioma invasion observed in brain parenchyma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 56 publications
4
87
0
Order By: Relevance
“…Although it has long been assumed that haematogenous spread accounts for virtually all UM metastasis, liver metastases may appear months to many years after diagnosis of the primary tumour . This temporal variation and latency in the appearance of metastases could be explained by (1) the formation of dormant metastases after intravascular spread and/or (2) extravascular migratory metastasis (EVMM), or step‐by‐step migration from the primary tumour to the site of metastasis ; this has also been reported in other tumours . Tumour cell dormancy in UM may be secondary to a number of mechanisms, such as escape from immune surveillance in the space of Disse , angiogenesis , or tumour cell kinetics .…”
Section: Introductionmentioning
confidence: 99%
“…Although it has long been assumed that haematogenous spread accounts for virtually all UM metastasis, liver metastases may appear months to many years after diagnosis of the primary tumour . This temporal variation and latency in the appearance of metastases could be explained by (1) the formation of dormant metastases after intravascular spread and/or (2) extravascular migratory metastasis (EVMM), or step‐by‐step migration from the primary tumour to the site of metastasis ; this has also been reported in other tumours . Tumour cell dormancy in UM may be secondary to a number of mechanisms, such as escape from immune surveillance in the space of Disse , angiogenesis , or tumour cell kinetics .…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33] The heterogeneity between the vascular basement membrane and parenchyma has been modeled by layering matrix types, revealing distinct differences in migration depending on the composition of each layer. 34,35 Cells also rapidly follow anatomical tracks, modeled by micropatterned adhesive ligands and electrospun fibers. 36,37 For perivascular invasion specifically, microfluidic devices have been developed to investigate vascular homing and extravasation using separate chambers for endothelial cells, 3D matrix, and a cell reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…The mode of migration may be critical for how well tumor cells, including those in GBM, are able to invade the surrounding tissue and disseminate. Several recent studies found that GBM cells can migrate collectively 26,27 , although whether GBM CSCs specifically use this type of migration is an open question. Our data indicate that a variety of patient-derived GBM CSC models can move in small to large collectives away from tumor spheres plated on Geltrex, although CSCs can also migrate individually and as mixtures of single cells and collectives.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by the Friedl group demonstrated that human glioma cells can invade as multicellular groups, as well as individual cells, into 3D astrocyte scaffolds, mouse brain slice cultures, mouse brain xenografts, and in human tumor samples 26,27 . Specifically, glioma cells maintain cell-cell connections while moving along both blood vessels and the astrocyte-rich brain stroma 26 . Thus, we favor a model in which collective invasion of GBM CSCs helps disseminate tumors into the brain parenchyma and vasculature 60 , although this has yet to be directly tested.…”
Section: Discussionmentioning
confidence: 99%